2020
DOI: 10.17533/udea.vitae.v27n3a02
|View full text |Cite
|
Sign up to set email alerts
|

Drug interactions for elderly with respiratory disorders and times of COVID-19: a systematic scoping review

Abstract: Background: The elderly people have high morbimortality associated with respiratory disorders, in addition to the presence of other safety risk factors, such as the use of potentially inappropriate medication and the occurrence of drug interactions. Objective: Considering the current pandemic scenario, it was intended to identify explicit criteria-based tools that reported drug interactions between potentially inappropriate medication and respiratory system disorders and possibly worse prognosis of COVID-19 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…, β 2 -receptor antagonism), which worsens the respiratory condition and leads to respiratory depression. Choosing a cardio-selective beta-blocker is suggested in medical management[ 8 ] which is consistent with what has been suggested by Santillo and Migale in their review[ 2 ]. However, not all the tools propose therapeutic management.…”
Section: To the Editorsupporting
confidence: 69%
See 1 more Smart Citation
“…, β 2 -receptor antagonism), which worsens the respiratory condition and leads to respiratory depression. Choosing a cardio-selective beta-blocker is suggested in medical management[ 8 ] which is consistent with what has been suggested by Santillo and Migale in their review[ 2 ]. However, not all the tools propose therapeutic management.…”
Section: To the Editorsupporting
confidence: 69%
“…However, not all the tools propose therapeutic management. In the COVID-19 era, it is important to carefully assess treatment, taking account of drug interactions, and potentially inappropriate medications in the elderly to prevent the worsening of COVID-19 and other comorbidities[ 8 ]. Although several criteria to assessing inappropriate prescribing in elderly individuals ( i.e.…”
Section: To the Editormentioning
confidence: 99%
“…In some clinical settings in geriatric medicine, such as the management of patients with comorbidities or low life expectancy, the use of beta blockers should be carefully evaluated on a case-by-case basis. A recent systematic review demonstrated that beta blockers were a class of drugs, that if inappropriately used, could adversely affect the prognosis of COVID-19[ 60 ]. The review considered drugs with potential negative impact on respiratory diseases, such as asthma, chronic obstructive pulmonary disease and respiratory failure, and therefore expressed a preference for the use of selective beta blockers in the COVID-19 scenario.…”
Section: Beta Receptor Blockers For Elderly In the Context Of Covid-19mentioning
confidence: 99%